Repurposing inhibitors of phosphoinositide 3-kinase as adjuvant therapeutics for bacterial infections - Fleeman, Renee (Frontiers in Antibiotics, 2023)
The rise in antimicrobial resistance and the decline in new antibiotics has created a great need for novel approaches to treat drug resistant bacterial infections. Increasing the burden of antimicrobial resistance, bacterial virulence factors allow for survival within the host, where they can evade host killing and antimicrobial therapy within their intracellular niches. Repurposing host directed therapeutics has great potential for adjuvants to allow for more effective bacterial killing by the host and antimicrobials. To this end, phosphoinositide 3-kinase inhibitors are FDA approved for cancer therapy, but also have potential to eliminate intracellular survival of pathogens. This review describes the PI3K pathway and its potential as an adjuvant target to treat bacterial infections more effectively.